Motivasi Orang Tua dalam Memilih Hasanka Boarding School Palangka Raya: Studi Kasus Lembaga Pendidikan Islam untuk Muslim Ekonomi Menengah: Parental Motivation in Choosing Hasanka Boarding School Palangka Raya: A Case Study of an Islamic Educational Institution for the Middle-Class Muslim - Saefulloh, Ahmad; Arifin, Syamsul; Ishomuddin, Ishomuddin; Nalus, Syafrul; Zuzanti, Zakia; Sa'diah, Halimatus; Ningrum, Fitrianur Widya (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This article aims to analyze the factors influencing the decision-making process of Muslim parents from upper-middle economic backgrounds in selecting Islamic-based educational institutions in Palangka Raya. Hasanka Boarding School, as one of the most favored modern Islamic educational institutions, becomes the focus of this study, highlighting the need to examine the underlying reasons and motivations of parents in choosing this school. The research employed a mixed-method approach with case study, using closed-ended questionnaires for quantitative data collection and open-ended questionnaires for qualitative descriptive analysis. The study involved 55 respondents, all of whom are parents of students at Hasanka Boarding School Junior High School. The instrument items were developed based on the framework proposed by Abuddin Nata concerning the factors that influence parents in choosing Islamic education. The findings indicate that religious aspects (95%) are the dominant factor motivating parents to choose Hasanka Boarding School, followed by the quality of education and teachers (91,6%), as well as the school's role in supporting social development and future aspirations (90%). Meanwhile, the integrated curriculum and school reputation were found to be lower in the hierarchy of motivating factors. These findings were analyzed through the integration of several theoretical frameworks, including Maslow's theory of motivation, Lancaster's consumer choice theory, Islamic education theory, community-based education theory, and religious moderation theory. This study contributes to strengthening the understanding of the multidimensional factors that influence educational decisions among Muslim middle-class communities in the modern era.